Education and Irish society - with special reference to informational needs - Hyland, W. J. (Statistical and Social Inquiry Society of Ireland, 1971)
For the first time since the foundation of the State some data on the educational experience of the population were collected at the 1966 Census of Population, taken on the night of 17th April 1966. Information on age at which full-time education has ceased and on type of school or college attended (also on a full-time basis) was collected for all persons 14 years and over. As had been the custom in previous censuses of population, data on the type of education being received were collected also in respect of each person, 14 years and over, attending an educational institution on a full-time basis.
Read before the Society, 26 March 1971
Keywords: Education in Ireland; Human capital; Data availability; Data requirements; 314.15